The Effect of Business Partnerships, Product Diversification, and Market Competitiveness on MSME Business Performance in Jakarta - Loso Judijanto; Eva Yuniarti Utami; Muhammad Aga Sekamdo (West Science Journal Economic and Entrepreneurship, 2023)
The present study examines the intricate dynamics between product diversification, business partnerships, and market competitiveness as they pertain to the performance of Micro, Small, and Medium-sized Enterprises (MSMEs) in Jakarta. Employing a quantitative analysis approach, the study integrates Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to scrutinize a sample of 150 MSMEs. The measurement model establishes the reliability and validity of the selected constructs, demonstrating robust factor loadings, high reliability, and satisfactory convergent validity. Discriminant validity analysis ensures the distinctiveness of the constructs, while model fit indices affirm the appropriateness of the Estimated Model in capturing observed data patterns. The structural model analysis reveals significant positive relationships between business partnerships, market competitiveness, and product diversification with MSME business performance. These findings hold valuable implications for policymakers, providing insights into the targeted interventions needed to bolster the MSME sector in Jakarta.